Local policies and the European Social Fund : employment policies across Europe - Zimmermann, Katharina (Research in comparative & global social policy., 2019)
Comparing data from 18 local case studies across 6 European countries, and deploying an innovative mixed-method approach, this book presents comparative evidence on everyday challenges in the context of the European Social Fund (ESF) and discusses how these findings are applicable to other funding schemes.